Modeling Hourly Productivity of Advanced Practice Clinicians in the Emergency Department - Bryan A. Stenson; Peter S. Antkowiak; David T. Chiu; Leon D. Sanchez; Joshua W. Joseph (Western Journal of Emergency Medicine)
Introduction: Advance practice clinicians (APC) play significant roles in academic and community emergency departments (ED). In attendings and residents, prior research demonstrated that productivity is dynamic and changes throughout a shift in a predictable way. However, this has not been studied in APCs. The primary outcome of this study was to model productivity for APCs in community EDs to determine whether it changes during a shift similar to the way it does for attendings and residents. Methods: This was a retrospective, observational analysis of 10-hour APC shifts at two suburban hospitals, worked by 14 total individuals. We examined the number of patients seen per hour of the shift by experienced APCs who see all acuity and staff all patients with an attending. We used a generalized estimating equation to construct the model of hour-by-hour productivity change. Results: We analyzed 862 shifts over one year across two sites, with three shift start times. Site 1 10 am–8 pm saw an average of 13.31 (95% confidence interval [CI] 13.02–13.63) patients per shift; Site 2 8 am–6 pm saw an average of 12.64 (95% CI 12.32–13.06) patients per shift; Site 2 4 pm–2 am saw an average of 12.53 (95% CI 12.04–12.82) patients per shift. Across all sites and shifts, hour 1 saw the highest number of patients. Each subsequent hour was associated with a small, statistically significant decrease over the previous hours. This was most pronounced in the shift’s last two hours. Conclusion: The productivity of APCs demonstrates a similar pattern of hourly declines observed in both resident and attending physicians. This corroborates prior findings that patients per hour is a dynamic variable, decreasing throughout a shift. This provides further external validity to prior research to include both APCs and community EDs. These departments must take this phenomenon into account, as it has scheduling and operational consequences.